Ethical and counseling challenges in prenatal exome sequencing. (11th September 2018) - Harris, Sarah; Gilmore, Kelly; Hardisty, Emily; Lyerly, Anne Drapkin; Vora, Neeta L.
Abstract: Objective: Ethical and counseling challenges are expected with the introduction of prenatal whole exome sequencing. In this study, we describe specific challenges identified through the UNC‐Chapel Hill Prenatal Exome Sequencing Study. Methods: Participants were a subset of women participating in the fetal exome study, which has enrolled 73 mother‐father‐fetus trios in pregnancies diagnosed with structural anomalies and normal standard genetic testing results. In this descriptive study, cases were reviewed by members of the research team, including a bioethicist, to identify counseling challenges. Illustrative cases were chosen by group consensus. Results: Four illustrative cases were identified for further analysis. Challenges included need for adequate counseling and informed consent, challenges in prenatal variant interpretation, performing prenatal diagnosis in subsequent pregnancies, inability to identify a genetic etiology, and identifying parental secondary findings. Conclusion: Our study illustrates several challenges identified in an ongoing prenatal exome study. While genomic medicine is a powerful tool for prenatal diagnosis, it is important that clinicians understand the ethical implications and parental perceptions of this testing modality. Abstract : What's already known about this topic? Next generation sequencing, including whole exome sequencing, is revolutionizing the field of clinical genetics. Many unique challenges are expected as this technology becomes more widespread in the prenatal setting. What does this study add? We highlight ethically complex counseling challenges identified through an ongoing fetal exome sequencing study, including the need for adequate counseling and informed consent, counseling challenges related to return of uncertain results, prenatal testing in future pregnancies, and identification of secondary findings.